The Implementation of National Environmental Management Policy at a Rural University in the Eastern Cape Province, South Africa - Vuyokazi Momoti (E-Journal of Humanities, Arts and Social Sciences, 2023)
The objective of the study was to investigate the challenges associated with carrying out the National Environmental Management Policy at a distant university in the Eastern Cape Province. The purpose of the study was to gain a better understanding of the university’s environmental management practices. The qualitative part of the investigation was a case study using convenience sampling. Ten managers who implement policies in their departments were chosen as participants in the case study. Phone interviews were also conducted in 2021 due to the COVID outbreak. Data analysis used content analysis. The results indicated that the university’s implementation of the national environmental management policy lacked clarity. The study suggests that the university should create and implement an environment management policy for employees to use as a reference. Furthermore, managers should focus on using effective environmental tools and effective communication strategies. The institution should provide management with tools to explain clear directives under the National Environmental Management Act of 1998.